Recent Advances on Clonal Forestry in West Bengal - Chakrabarti, Kalyan; Barari, S. (Indian Forester, 1998)
The paper gives a detailed account of the successes and failures of the clonal propagation attempts in the State of West Bengal and the overall result of clonal forestry tends to indicate its effectiveness in enhancing the productivity of the West Bengal forests. An increment of about 2.86 m in height was observed from a clonal plant in the first year brought from Bhadrachalam and planted in South Bengal in respect of Eucalyptus tereticornis, which is quite promising. The results of clonal forestry in other regions of the State also are quite encouraging and are likely to meet the desired expectation of optimising productivity in the forests.